O empoderamento feminino frente ao processo de parto e nascimento: percepções e vivências maternas e a importância do profissional de saúde - BRITO, Stelacelly Coelho Toscano de (2019)
INTRODUCTION: The Ministry of Health in order to structure and reorganize the maternal and child care assistance proposes a new approach focusing on women and the rescue of the birthing process, in contrast to the biomedical model that is often employed to society. Then, it is extremely necessary to rescue humanized aspects and enhance the mother's position, as well as the role of health care professionals to advise and instruct them. AIMS: The goal of this study is to investigate the perception of women about empowerment during labor and birthing process. METHODOLOGY: This is a descriptive study with a qualitative approach, performed in the Rooming-in area at the Sacred House of Mercy Foundation Hospital of Pará (FSCMPA). The subjects of this study were 17 women, between 18 and 35 years old, who experienced vaginal delivery in the institution. It was applied semi-structured interview, from June to July 2016. The data analysis was conducted following the content analysis technique. This study followed the rules established for research with human beings (Resolution 466/2012). RESULTS AND DISCUSSION: Emerged two drivers cores, the first one was related to the perceptions about women's empowerment in labor and birth, which was evident pain, emotional unpreparedness and fear as obstacles to women's empowerment. In contrast, the experiences of previous pregnancies and the exchange of knowledge among women, contributed to strengthen and women's emporwerment. The second driver core addressed the importance of health care professionals in maternity care, however to do this, it is necessary that the professional is committed to enhancing the capacity and maternal participation. The quality of care has emerged in a relevant way in the study, but in the context of the construction of empowerment during labor in the hospital, not during the course of pregnancy in prenatal care. CONCLUSION: Therefore, despite the advances noted in the care model, it is highlighted that health professionals need to empower women in order to help them to develop participatory power in the women's empowerment process, especially during prenatal care. Thereby providing understanding to women about their rights and their ability to empower themselves.